تأثير التفاعل الاجتماعي في مهارة الكلام: المراجعة المنهجية للأدب حول تعليم اللغة العربية بوصفها لغةً ثانية - Ibad, Irsyadul; Khuluq, Ahmad Ahsanul (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
This article examines the influence of social interaction on the speaking skills and communicative competence of learners of Arabic as a second language through a PRISMA-based systematic literature review (SLR) of publications from 2015 to 2025. Of the 573 initial findings, 20 studies met the inclusion criteria and were analyzed thematically, covering interaction types (teacher–student, student–student, and digital), competency dimensions (linguistic, sociolinguistic, discourse, strategic), and learning designs. The synthesis shows that social interaction—both face-to-face and technology-mediated—consistently increases engagement, noticing, and pushed output, thereby strengthening language fluency and accuracy. These findings are consistent with the Input Hypothesis (Krashen) and the Interaction Hypothesis (Long) and confirm the role of the language environment as a mediator between interaction and communication achievement. In the context of Gen Z and the digital ecosystem, online communities expand language exposure beyond the classroom but require digital literacy and multitasking management. Pedagogical implications include shifting the teacher's role to that of a social facilitator, assigning collaborative tasks, explicitly integrating pragmatic exercises (speech acts, politeness), and utilizing interactive media. Research gaps include the need for cross-level longitudinal causal testing of proficiency and pragmatic outcome measurement. The findings provide applicable recommendations for the design of socially and digitally adaptive communicative curricula.